Modifications in aroma characteristics of ‘Merlot’ dry red wines aged in American, French and Slovakian oak barrels with different toasting degrees - Haocheng Lu; Binhao Cheng; Yibin Lan; Changqing Duan; Fei He (Food Science and Human Wellness)
Aging in oak barrels is widely used in enology which could bring flavor changes and aromatic complexity to wines. In the present study, the aroma compounds were analyzed from the ‘Merlot’ dry red wines, which were fermented in two types of fermenters (stainless steel tank and rotated oak barrel) and aged in six types of oak barrels (three geographic origins × two toasting degrees) for different time (0, 3, 6 and 9 months, respectively). Results showed that 30 volatiles were associated with barrels and increased during oak aging. The fermenters could influence the intensities of the toast, leathery, smoky, fruity, floral and caramel aromas. The concentration of whisky lactone, eugenol, cis-isoeugenol, and the intensities of the toast and spicy aromas were highest in the wines aged in American oak and were lowest in the wines aged in French oak barrels. The concentrations of guaiacol, syringol, trans-isoeugenol, furfural alcohol, vanilla, cis-whisky lactone enabled the medium toasting barrels to be distinguished from the light toasting ones. The compounds originating from the barrels could be used to distinguish the types of different barrels, but the other general grape-derived and fermentation-derived volatiles could not. The fermenters, oak species and toasting degrees of the barrels all had significant effects on the aroma profiles of the aged ‘Merlot’ dry red wines, but the influence of the geographic origin was not obvious.